Evaluation of the Histological Effects of Allium Cepa Administration on the Prostate Histology and Prostate Specific Antigen of Male Albino Rats Induced with Ciprofloxacin - Mathew, Uwuigbe; Ohiwerei Wisdom Omogbai; Edebiri Ogbemudia E; Ajanwachukwu Ogbonna Wilson; Oriahoghen E E (International Journal of Applied and Scientific Research, 2024)
The primary objective of this study is to assess the histological impact of Allium cepa administration on prostate histology and prostate-specific antigen (PSA) levels in male albino rats that were induced with ciprofloxacin. A total of 100 albino rats, each weighing between 150–250g, were used in the experiment. The experimental group was further divided into four subgroups, each containing 10 rats, labeled as Groups A, B, C, D, and E. Group A served as the control, while Group B received only ciprofloxacin. Group C was administered ciprofloxacin along with 100mg of Allium cepa extract, whereas Group D received ciprofloxacin and 200mg of Allium cepa extract. Group E was treated solely with Allium cepa extract. Groups B, C, and D were given 22.86 mg/kg of oral ciprofloxacin (500 mg/tablet), manufactured by Fidson Health Care Ltd. The ciprofloxacin was obtained from a reputable pharmaceutical store in Ekpoma, Edo State, and administered via gavage. The control group was provided with only water and food. The PSA levels in control and test subjects were recorded as Mean ± SEM. For the control group, the PSA level was 0.6250 ± 0.085 ng/ml. The PSA levels for test groups B, C, D, and E were 1.575 ± 0.417 ng/ml, 1.200 ± 0.123 ng/ml, 1.125 ± 0.048 ng/ml, and 3.300 ± 0.835 ng/ml, respectively. Notably, only Group E exhibited a significant increase (P<0.05) in PSA levels when compared to the control group.In conclusion, this study indicates that exposure to ciprofloxacin and Allium cepa at mild or moderate doses can lead to severe histopathological changes in the testis, prostate, and epididymis, with the exception of the brain